Control of active lower limb prosthesis using human-in-the-loop scheme. Issue 1 (31st December 2022) - Hernández, Iván; Yu, Wen
Abstract: In many cases robots are directly in touch with humans, this interaction is necessary to design control systems that take into account a human-machine relation. Particularly important is the case when humans share the control with a robot. So, in order to validate control schemes, it is necessary to test them in an environment where the human-machine interaction exists, what could be even dangerous for humans. We present a model of human useful to test controllers, and propose a scheme for human-in-the-loop under shared control. We test the model and the scheme in a lower limb prosthesis that implies naturally a human-machine interaction. Apart from this research, we propose an efficient and low-cost controller for the prosthesis, based on a sensory exoextension and a neuro-decoder consisting of a multilayer perceptrons. The results show the effectiveness of human model to emulate the human interaction.